Cultural beliefs and practices of Sri Lankan public as experienced by clinicians - Chandratilake, M.; Jayarathne, Y.G.S.W.; Karunarathne, D. (Sri Lanka Medical Association, 2017)
INTRODUCTION & OBJECTIVES: Sri Lankan society is culturally diverse. Cultural beliefs and practices impact heavily on health seeking behaviour of the public, their compliance with treatment and the ultimate health outcome. The aim of this study was to explore the cultural practices of the Sri Lankan public as experienced by clinicians. METHODS: The topic warranted a qualitative design. Individual face-to-face interviews were conducted with 30 clinicians, who represented a range of specialties and subspecialties, and worked in teaching hospitals at Ragama and Anuradhapura. They were audio-recorded and transcribed verbatim. The transcripts were thematically analysed using Richie and Spencer framework. RESULTS: Key aspects (themes) of cultural practices among the public were identified. Although they are not exclusive the origin of healthcare-related cultural practices included religious beliefs and societal norms in the community one lives in, personal experiences and traditional medicine. Cultural issues originating from all the above sources were observed across specialties and subspecialties. The existence of beliefs and practices has been influenced by personal conviction, the family and society. The cultural beliefs and practices are related to nutrition, physiological events and disease conditions, which include the origin, the manifestations and the prevention of such diseases. The response of clinicians toward such beliefs and practices appeared to be passive or negative. CONCLUSION: The origin of cultural beliefs appears to be the community. The collectivist nature of Sri Lankan culture appears to facilitate their existence. Cultural beliefs and practices affect both health and disease which could be dealt with more positively by clinicians for a better patient outcome.
Oral Presentation Abstract (OP 007), 130th Anniversary International Medical Congress, Sri Lanka Medical Association, 13th-16th July 2017 Colombo, Sri Lanka
Keywords: Cultural beliefs